Configurable, Hierarchical, Model-based, Scheduling Control with photovoltaic generators in power distribution circuits. (April 2015) - Jung, Jaesung; Onen, Ahmet; Russell, Kevin; Broadwater, Robert P.; Steffel, Steve; Dinkel, Alex
Abstract: Existing distribution systems and their associated controls have been around for decades. Most distribution circuits have capacity to accommodate some level of PV generation, but the question is how much can they handle without creating problems. This paper proposes a Configurable, Hierarchical, Model-based, Scheduling Control (CHMSC) of automated utility control devices and photovoltaic (PV) generators. In the study here the automated control devices are assumed to be owned by the utility and the PV generators and PV generator controls by another party. The CHMSC, which exists in a hierarchical control architecture that is failure tolerant, strives to maintain the voltage level that existed before introducing the PV into the circuit while minimizing the circuit loss and reducing the motion of the automated control devices. This is accomplished using prioritized objectives. The CHMSC sends control signals to the local controllers of the automated control devices and PV controllers. To evaluate the performance of the CHMSC, increasing PV levels of adoption are analyzed in a model of an actual circuit that has significant existing PV penetration and automated voltage control devices. The CHMSC control performance is compared with that of existing, local control. Simulation results presented demonstrate that the CHMSC algorithm results in better voltage control, lower losses, and reduced automated control device motion, especially as the penetration level of PV increases. Highlights: Control performance for high PV penetrations – 69%, 96%, and 123% – are investigated. Utility control devices create a baseline schedule against three prioritized objectives. PV generators are scheduled to support the baseline schedule. Quasi-steady state power flow simulations using 1 s PV measurements are run. Improvements in voltage control, losses, controller motion and violations are presented.